2019
DOI: 10.1016/j.ejphar.2019.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Multiple actions of fenamates and other nonsteroidal anti-inflammatory drugs on GABAA receptors

Abstract: The nonsteroidal anti-inflammatory drug (NSAID) niflumic acid, a fenamate in structure, has many molecular targets, one of them being specific subtypes of the main inhibitory ligand-gated anion channel, the GABA A receptor. Here, we report on the effects of other fenamates and other classes of NSAIDs on brain picrotoxinin-sensitive GABA A receptors, using an autoradiographic assay with [ 35 S]TBPS as a ligand on mouse brain sections. We found that the other fenamates studied (flufenamic acid, meclofenamic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Atovaquone is a naphthoquinone‐bearing compound, and has been reported to have inhibitory activity against both human DHODH and rat DHODH, but the IC 50 value for rat DHODH inhibition is much lower than that for human DHODH inhibition (Knecht et al, 2000). Tolfenamic acid, niflumic acid, and mefenamic acid are all fenamate nonsteroidal anti‐inflammatory drugs (NSAIDs) (Mansikkamaki et al, 2019). A number of fenamic acid derivatives have been discovered to have potent hDHODH inhibitory activities through structure‐guided fragment selection and virtual screening (Fritzson et al, 2010; Walse et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Atovaquone is a naphthoquinone‐bearing compound, and has been reported to have inhibitory activity against both human DHODH and rat DHODH, but the IC 50 value for rat DHODH inhibition is much lower than that for human DHODH inhibition (Knecht et al, 2000). Tolfenamic acid, niflumic acid, and mefenamic acid are all fenamate nonsteroidal anti‐inflammatory drugs (NSAIDs) (Mansikkamaki et al, 2019). A number of fenamic acid derivatives have been discovered to have potent hDHODH inhibitory activities through structure‐guided fragment selection and virtual screening (Fritzson et al, 2010; Walse et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, fenamates are unique because they are both anti-inflammatory and highly subunit-selective modulators of GABA A receptors at low micromolar concentrations (Halliwell et al, 1999;Mansikkamäki et al, 2019;Rossokhin et al, 2019). These NSAIDs also cross the blood brain barrier indicating that they have central nervous system actions.…”
Section: Discussionmentioning
confidence: 99%
“…Work from this lab, for example, first reported that mefenamic acid potentiates GABA A -receptor mediated currents recorded from recombinant human α1β2γ2 receptors expressed in Xenopus oocytes and HEK-293 cells but inhibits GABA currents recorded from α1β1γ2 GABA A receptors in these expressions systems (Halliwell et al, 1999). Similarly, niflumic acid potentiates recombinant rat α1β3γ2 GABA currents recorded from Xenopus oocytes but inhibits α1β1γ2 GABA mediated responses (Mansikkamäki et al, 2019). Point mutation experiments and molecular modeling show that potentiation of GABA A receptors by fenamates occurs via an allosteric site in the transmembrane 2 domain of the β2 and β3 subunits shared with the general anaesthetic, etomidate and the antiseizure agent, loreclezole (Halliwell et al, 1999;Mansikkamäki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations